Integrative causal inference illuminates gene-environment interactions linking endocrine disruptors to female infertility - Yanggang Hong; Zhuoyi Du; Jiajun Li; Yi Wang; Yirong Wang; Wanyi Shu; Qinxi Shen; Feng Chen; Sisi Li (Ecotoxicology and Environmental Safety, 2025)
Female infertility, a global health concern affecting up to 12 % of women, is influenced by genetic, hormonal, and environmental factors. Among environmental contributors, endocrine-disrupting chemicals (EDCs), which interfere with hormonal systems, have gained attention for their potential impact on reproductive health. This study used Mendelian randomization (MR) and colocalization analyses to explore the causal relationships between gene expression influenced by EDCs and female infertility. We identified 4207 EDC-related genes from The Endocrine Disruption Exchange (TEDX) database and Comparative Toxicogenomics Database (CTD), and analyzed their potential causal effects on female infertility using genome-wide association data. A total of five genes showed significant associations with infertility risk, with SULT1B1, MASTL, and TTC39C linked to increased risk, and ESR1 and AKAP13 associated with a protective effect. Colocalization analysis revealed that four of these genes (ESR1, TTC39C, AKAP13, and SULT1B1) shared causal variants with infertility, strengthening the MR findings. Additionally, interactions between these genes and key EDCs like bisphenol A (BPA), tetrachlorodibenzodioxin (TCDD), and sodium arsenite highlighted complex molecular mechanisms through which environmental exposures influence fertility. These findings provide new insights into the gene-environment interactions contributing to female infertility and offer potential targets for interventions to mitigate the harmful effects of EDCs on reproductive health.